La delibazione della sentenza ecclesiastica di nullità del matrimonio "post mortem coniugis" - Colla, Oriana ("Iustitia et iudicium" ; 4, 2010)
The writing from entitled "the enforcement proceedings of the ecclestiastical sentence of nullity of the marriage post mortem coniugis" has to object a theme to poorly explored today, that is the legitimation to act for the enfordement proceedings of the ecclesiastical sentence of nullity of the marriage after the death of the consort